Pentingnya Sosialisasi Manajemen Keuangan Rumah Tangga Guna Meningkatkan Taraf Kesejahteraan Masyarakat Rawang Kota Pariaman - Nichy Oktaviani; Asrul; Irni Yusnita; Sri Mulyani; Deby Handayani; Sudirman; Marshal Imar Pratama; Mexano Hans Gery; Zaki (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
Abstract A maximum of 150 Indonesian words printed in italics with Cambria 10 point. The abstract should be clear, descriptive and should provide a brief overview of community service issues undertaken / researched. Abstracts include reasons for the selection of topics or the importance of research topics / community service, methods of research / devotion and outcome summary. The abstract should end with a comment about the importance of the result or a brief conclusion.